Regulating negligence in German and in Spanish criminal law - GHIGHECI CRISTINEL (Juridical Tribune, 2018)
Abstract Although in German and in Spanish legal systems there are no express provisions with regard to the criminal negligence (culpa), this has not hindered the legal doctrine and jurisprudence to thoroughly analyse this form of guilt. This made it possible to qualify as intentional offences some deeds which in our legal system are considered to be committed with conscious negligence (involving foresight). The difficulty to distinguish between indirect intention (dolus eventualis) and conscious negligence (luxuria) has nonetheless determined Spanish courts to ask the legislator to provide a clear definition of indirect intention, which could be an additional argument with respect to the weaknesses entailed by such a legal approach. Keywords: criminal negligence, indirect intention, German legal system, Spanish legal system. JEL Classification: K14